Efektivitas Layanan Bimbingan Belajar Untuk Meningkatkan Konsentrasi Belajar Siswa SMP Negeri 1 Tapian Nauli - Riossally Marselina Tumanggor; Sarinaiba Situmeang; Henokh Granto Sinaga; Asnida Asnida; Nanny Natania Lumbantobing; Tulus Nababan; Ridana Laia; Januaris Pane (Utan Kayu Publishing, 2022)
This activity is to improve the academic climate that is creative, innovative, visionary, solutive and independent and to improve the quality of students in higher education so that later they can become members of the community who have academic and professional abilities who can apply, develop and disseminate science, technology and art as well as enrich the national culture. This Community Service (PkM) activity was carried out at SMP Negeri 1 Tapian Nauli, Jalan Sibolga-Barus KM 0.8 Tapian Nauli, Central Tapanuli Regency. Community service activities are carried out from 02 to 26 February 2022. Not all learning that takes place in schools can be accepted and understood by students. Every activity carried out is expected to provide benefits, as well as community service activities organized by the HKBP Nommensen Medan FKIP Student Team. This community service activity is expected to increase the enthusiasm for learning for students at SMP Negeri 1 Tapian Nauli.